African Elephant Specialist Group report/ Rapport du Groupe des Specialistes des Elephants d'Afrique - Holly Dublin (Pachyderm)
Reviews activities of the AfESG and associated programmes/projects related to elephant management/conservation, including development of the national elephant stategy for Ghana, the anticipation of additional national programmes, and the possibility of a subregional strategy for Central Africa; the development of the AfESG Website; the housing of available hard copies of the African Elephant Library (on the internet known as the African elephant Bibliography) at the Nairobi office; current status of MIKE and ETIS, and results of the Human-Elephant Conflict Taskforce.